PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA CV. MULIA ABADI - Fatahuddin; Armansyah (MBISKU: Jurnal Manajemen Bisnis dan Keuangan, 2024)
This quantitative research aims to highlight the influence of work discipline on employee performance. Using SPSS 24 to analyze data, this research uses various analytical techniques including research instrument testing, classical assumption analysis, simple linear regression analysis, hypothesis testing, coefficient of determination, and t test. This research uses a quantitative approach, focusing on the relationship between work discipline and employee performance. The sample consists of the entire population of 35 employees, using non-probability sampling techniques with a census approach. The research results show that good work discipline has no influence and is not significant on employee performance. The coefficient of determination (R Square) of 0.690 indicates that work discipline explains 69% of the variation in employee performance, while 31% of dependence is influenced by other variables not included in this study. This research provides a deeper understanding of the relationship between work discipline and employee performance, as well as providing importance for management in improving employee performance in the organization.